CRITICAL SUCCESS FACTORS OF A SUBURBAN HOMESTAY: INSIGHT OF DESA CINTA KOBUNI HOMESTAY IN INANAM, SABAH, MALAYSIA - Liza Longgat; Spencer Hedley Mogindol, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Several homestays in Malaysia are located in rural regions with the goal of providing guests with a genuine rural living experience and enhancing the economic well-being of local residents. While research on homestays in rural regions is increasing, there is a lack of studies on homestays in suburban settings. Founded in 2017, Desa Cinta Kobuni (DCK) Homestay, situated in a suburban region in Kota Kinabalu, Sabah, has achieved many significant successes. This research intends to examine the practices and success factors identified by stakeholders of Community-Based Tourism (CBT) in a suburban area, with a specific emphasis on DCK Homestay. This research used a qualitative technique to connect with ten key stakeholders of DCK Homestay, interviewing them to acquire insights into their views and experiences. The data was analysed using theme analysis, identifying four crucial characteristics - people, process, strategy, and enabler - that have significantly influenced the success factors of DCK Homestay. Key factors contributing to the success of CBT were effective collaboration with neighbouring villages, mutual support via frequent meetings, and the development of community culture. Collaborative projects and activities with other communities were seen as crucial factors in improving the overall tourist experience. DCK Homestay's success was attributed to creative relationships, community participation, sustainable methods, and cultural promotion. These factors have enhanced the favourable view of CBT in a suburban environment and promoted mutual support and cultural interaction among community members. This research illuminates the distinctive characteristics of suburban cognitive-behavioural therapy, with a focus on DCK Homestay. The results highlight how community engagement, sustainable methods, and smart collaborations are crucial for the success of suburban CBT projects. Stakeholders can improve the tourist experience, help the local community, and promote the cultural diversity of the area by comprehending and using these important variables.